Investigating the neural correlates of affective mentalizing and their association with general intelligence in patients with schizophrenia - Tantchik, Wladimir; Green, Melissa J.; Quidé, Yann; Erk, Susanne; Mohnke, Sebastian; Wackerhagen, Carolin; Romanczuk-Seiferth, Nina; Tost, Heike; Schwarz, Kristina; Mößnang, Carolin Ulrike; Bzdok, Danilo; Meyer-Lindenberg, Andreas; et al. (Schizophrenia research, 2023)
Background and hypothesis - Mentalizing impairment in schizophrenia has been linked to altered neural responses. This study aimed to replicate previous findings of altered activation of the mentalizing network in schizophrenia and investigate its possible association with impaired domain-general cognition. - Study design - We analyzed imaging data from two large multi-centric German studies including 64 patients, 64 matched controls and a separate cohort of 300 healthy subjects, as well as an independent Australian study including 46 patients and 61 controls. All subjects underwent functional magnetic resonance imaging while performing the same affective mentalizing task and completed a cognitive assessment battery. Group differences in activation of the mentalizing network were assessed by classical as well as Bayesian two-sample t-tests. Multiple regression analysis was performed to investigate effects of neurocognitive measures on activation of the mentalizing network. - Study results - We found no significant group differences in activation of the mentalizing network. Bayes factors indicate that these results provide genuine evidence for the null hypothesis. We found a positive association between verbal intelligence and activation of the medial prefrontal cortex, a key region of the mentalizing network, in three independent samples. Finally, individuals with low verbal intelligence showed altered activation in areas previously implicated in mentalizing dysfunction in schizophrenia. - Conclusions - Mentalizing activation in patients with schizophrenia might not differ compared to large well-matched groups of healthy controls. Verbal intelligence is an important confounding variable in group comparisons, which should be considered in future studies of the neural correlates of mentalizing dysfunction in schizophrenia.